Experience of Using a New Brain Surgery Head Frame and Location Sticker for Treating Spontaneous Intracranial Hematoma - Wang, Hongyu; Xin, Wenqiang; Cui, Jianzhong (Frontiers in Neurology, 2022)
Objectives Various stereotactic aspirations have been accepted; however, no standard stereotactic aspiration has been established for the treatment of spontaneous intracerebral hemorrhage (ICH). The authors explored an easy, fast, and effective procedure by using a new brain surgery head frame and location sticker for the removal of spontaneous hematoma. Patients and Methods A retrospective database review was performed from January 2018 to March 2020 to identify patients with ICH who were treated with puncture and drainage for hematoma by using a new brain surgery head frame and location sticker for positioning and guidance. Results A total of 45 patients with spontaneous ICH were enrolled in our study. The mean (± SD) surgical time was 29.3 ± 4.1 min. The average hematoma evacuation rate was 72.2%. The mean (± SD) preoperative Glasgow Coma Scale (GCS) score was 9.58 ± 2.92; the mean GCS score increased to 11.55 ± 2.59 (p = 0.006) and 12.86 ± 2.04 (p < 0.001) at 1 week after surgery and at the time of discharge, respectively. The mean (± SD) preoperative muscle force score was 1.25 ± 1.51; the mean muscle force score had improved to 2.20 ± 1.64 (p = 0.009) and 2.88 ± 1.64 (p < 0.001) at 1 week after the operation and the time of discharge, respectively. Out of these, one patient experienced postoperative rebleeding, however, no further hematoma expansion was found after the second aspiration and thrombolysis. Conclusion Using this brain surgery, head frame and location sticker combined with urokinase infusion appears simple, safe, and effective for the removal of hematoma for patients with spontaneous ICH. However, randomized controlled trials are necessary to provide more concrete evidence-based results.